Impact of temperature and stresses distribution of brazed joints on durability of automotive radiators - Peta, Katarzyna; Grochalski, Karol; Wiśniewski, Marcin; Żurek, Jan (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2017)
The paper contains the major factors determining the durability of brazed joints used in automotive radiators. Particular attention was paid to the thermal stresses which are caused by uneven temperature distribution in the material during their exploitation. For this, the results of measurements of stresses in radiators, supplemented by temperature measurements by the thermocouples, were presented. The research was conducted in different exploitation conditions, mainly by changing the temperature of the air ß owed over the car cabin. Moreover, was compared the obtained results of measurements of brazed joints, complemented by observations and measurements of tightness. The summary contained a justiÞ cation of expediency analysis of assembly brazed joints. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)